A brief look at the Malaysian Prime Ministers'leadership styles / Nasrudin Mohammed - Mohammed, Nasrudin (Universiti Teknologi MARA, Shah Alam, 2005)
Leaders' style in leading are varied. Basically, as far as the classical view of leadership style is concerned, a leader's style can either be (1) democratic; (2) autocratic; or perhaps (3) laissezfaire. However, it is almost impossible to come up with a collectively agreeable conclusion of what a prime minister leadership style really is. There are a number of reasons for such pessimistic statement. First, leadership in general is often associated with conflict. One person's ideas and plans are put into collective action by a group or groups of people of which that one person had, in some way or another, managed to convince. Leadership, in this instance, is looked at how abstracts are put into concrete actions. It displays the ability of an individual to influence, motivate, and enable others to contribute (House, 2004:15). Therefore, in one sense, ideally, leadership is best defined by those who are directly involved in the whole process of achieving specific tasks that has been set out by individual or individuals on behalf of the institution or organisations. The leadership style of a leader, then, is rests upon the followers to determine. However, this should not prevent people outside the setting from making their own interpretations and conclusions.